Exploring the research trend and development of sports science technology in the last 4 decades: systematic review - Andhega Wijaya; Muchamad Arif Al Ardha; Nurhasan Nurhasan; Chung Bing Yang; Ru Han Lin; Andika Bayu Putro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study systematically reviews the trends and developments in sports science technology over the past four decades. Utilizing a comprehensive systematic review analysis of 1,127 articles from the SCOPUS database, we aimed to identify key subject areas, contributing countries, and prevailing keyword patterns in the field. The analysis highlights a significant increase in publications and citations, indicating the growing importance and recognition of sports science technology. Japan leads in contributions with the highest number of publications and citations, followed by the United States and China. Medicine and engineering emerged as the most influential subject areas, underscoring the interdisciplinary nature of the research. Keyword analysis revealed a strong emphasis on human studies, sports, and the integration of science and technology, reflecting the field's evolving landscape. Findings show that technological advancements such as sensor technology, big data analytics, and virtual reality have revolutionized sports science by enhancing performance monitoring, injury prevention, and rehabilitation processes. The study identifies critical trends and provides insights into future research directions, advocating for continued interdisciplinary collaboration and global cooperation to further advance the field. These insights offer a comprehensive overview of the historical and current state of sports science technology, serving as a roadmap for future innovations and applications. By understanding the development and current trends in sports science technology, researchers and practitioners can better plan and implement effective strategies for improving athletic performance and health, ultimately contributing to the broader field of sports science and technology.